The reproductive of sheep production in Indonesia : a research project - D. Sastradipradja; S. Partodihardjo (Media Veteriner, 1977)
The sheep seems to be a suitable and socio-economically acceptable animal for livestock production in Indonesia due its small and size and certain physiological characteristics of sheep whith say offer adventages for rearing over larger ruminants. The sheep population is however declining up to present. One way for improvement of sheep production has been attempted through crossbooring with imported breeds.A research project on certain aspects of sheep reproduction is discussed with omphasis on plasma reproduction hormonal levels, and with emphasis on plasma reproduction hormonal levels, and with the ultimate objective to rapidly increase the presently declining sheep population.